2018
DOI: 10.3390/molecules23112897
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Solubilization by Bacillus Species

Abstract: Microbial solubilization applies the natural ability of a microorganism to liberate phosphorus from unavailable structures. The main mechanism recognized to be responsible for the solubilization of phosphorus is the production of different types of organic acids. Three kinds of Bacillus species and three types of raw materials (poultry bones, fish bones, and ash) were tested for solubilization. The following parameters were compared for all discussed cases: pH, specific growth rate, solubilization factor, rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(97 citation statements)
references
References 29 publications
5
86
0
6
Order By: Relevance
“…A wide study was conducted on the increase in the nutrient supplement for plant growth, where the microbes solubilize the insoluble form of minerals and increase the availability of nutrients to plants [41]. Many Bacillus species were reported to be a potassium, phosphate, and zinc solubilizer, and their solubilizing ability was strongly influenced by production of organic acids [42]. Even B. megaterium from the phylloplane of Jatropha curcas was found to have an ACC deaminase activity, IAA production, and phosphate solubilization ability [43].…”
Section: Discussionmentioning
confidence: 99%
“…A wide study was conducted on the increase in the nutrient supplement for plant growth, where the microbes solubilize the insoluble form of minerals and increase the availability of nutrients to plants [41]. Many Bacillus species were reported to be a potassium, phosphate, and zinc solubilizer, and their solubilizing ability was strongly influenced by production of organic acids [42]. Even B. megaterium from the phylloplane of Jatropha curcas was found to have an ACC deaminase activity, IAA production, and phosphate solubilization ability [43].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus is the second most important nutrient after nitrogen that limits the growth and yield of crop plants. Plants can take up phosphorus in the form of HPO 4 2− and H 2 PO 4 − (Saeid et al ) but much of the phosphorus present in soil is unavailable to plants. Many soil micro‐organisms are endowed with the ability to solubilize unavailable form of phosphorus to available form and/or to mineralize organic phosphorus to available form of phosphorus (Bhattacharyya and Jha ) and are collectively called as phosphorus solubilizing micro‐organisms (PSMs).…”
Section: Bacillus and Phosphorus Nutritionmentioning
confidence: 99%
“…Three species of Bacillus viz., B. megaterium , B. subtilis and B. cereus were tested for solubilization of phosphorus in the substrates like poultry bones, fish bones and ash. All the three species produced organic acids and there was a strong correlation between total concentration of organic acids produced and the amount of available phosphorus released from the substrates (Saeid et al ). As opposed to soils with high pH where P is fixed as calcium phosphate, in acidic soils P is often complexed with aluminium and iron.…”
Section: Bacillus and Phosphorus Nutritionmentioning
confidence: 99%
“…Results from 16S ribosomal RNA (rRNA) sequencing of bacterial colonies revealed that the 16S rRNA genes of these bacterial colonies shared 96.22% and 89.18% identity to that of C. acnes NCTC 10390 and that of Bacillus shackletonii (B. shackletonii) LMG 18435, respectively (Supplemental Figure S2). The known abilities of Bacillus species to solubilize CaP [48][49][50][51] demonstrated the feasibility of using Pikovskaya's agar plates to select CaP-solubilizing bacteria from human skin. The identified C. acnes strain [10 5 colony-forming unit (CFU)] was incubated in phenol red-containing rich media in the presence of 2% glucose under anaerobic conditions for 10 days.…”
Section: Acnes Fermentation and Cap Solubilization By Fermentationmentioning
confidence: 99%